Youth in the making : the skin-care promise - Lau, Hui Chwen; Lee, Siew Chin (Fakulti Sains Sosial dan Kemanusiaan, Universiti Kebangsaan Malaysia, 2018)
This study focuses on the marketing strategies used to persuade or attract buyers in beauty advertisements. The ideal in beauty is seen in having healthy youthful complexions. Hence it has become a commercial commodity globally. This study sets out to explore and identify activities which are geared towards making oneself beautiful. The activities involved in making one attractive is cultural to the concept of beauty, and this is framed in the advertisements of beauty products. In this study a purposive sampling is used to analyse how marketing strategies framed the concept of beauty in the selected skin care products. Three categories of beauty products are selected and analyzed at the macro-micro levels. Lewis’ AIDA model (1898) which spelled out the strategies for marketing is used together with Roderiguez and Dimitrova’s framework for media framing (2011) to analyse how skin-care products are strategized in cosmetic advertisements. The findings indicated that the ideological views of beauty are strategically framed with the promise of looking young.